The answer is 1/4 because all you have to really do is simplify
Answer:
8 1/30
Step-by-step explanation:
Calculate by converting into improper fractions.
Answer:
m = x+y-z
Step-by-step explanation:
Given the expression.
(a^x a ^y) ÷ a^z = a^m
We are to express m in terms of x, y and z.
Using the multiplicative law of indices, the expression becomes:
a^{x+y} ÷ a^z = a^m
Applying the division rule in indices
a^{x+y} ÷ a^z = a^{x+y-z}
The equation becomes
a^{x+y-z} = a^m
Cancel out the base and equate the powers as shown:
x+y-z = m
Hence the expression of m in terms of x, y and z is m = x+y-z
Answer:
12. DE
13. DE
14. BE
15. DE
16. BC
Step-by-step explanation:
A midsegment is a line drawn across a triangle from one side to another that is parallel to the third side. It is also half the length of the parallel side. Here it is called DE.